MANAJEMEN RANTAI PASOK KOMODITAS TOMAT PASCA PANDEMI COVID-19 DI DESA SIDERA KECAMATAN BIROMARU KABUPATEN SIGI - Dewi, Dewi; Kalaba, Yulianti; Laihi, Moh. Alfit A. (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
Tomatoes are a vital horticultural commodity with significant economic importance in many countries. This study aims to investigate the demand for tomatoes, analyze the flow patterns within the tomato supply chain, and examine the mechanisms of supply chain management and assess its efficiency in Sidera Village, Biromaru Subdistrict, Sigi District, in the post-Covid-19 period. The research employed both qualitative and quantitative descriptive methods. The findings indicate that post-Covid-19 tomato supply chain management is a complex system that requires coordination and integration of product flow, information flow, and financial flow throughout the distribution process.